The Insidensi dan Derajat Infeksi Anisakiasis pada Ikan Hasil Tangkapan di Pelabuhan Perikanan Pantai Muncar, Banyuwangi, Jawa Timur (INCIDENCE AND DEGREE OF ANISAKIASIS INFECTION IN FISH CATCHES AT THE FISHERY PORT OF MUNCAR BEACH, BANYUWANGI, EAST JAVA) - Ulkhaq, Mohammad Faizal; Budi, Darmawan Setia; Azhar, Muhammad Hanif; Kenconojati, Hapsari (Jurnal Veteriner; Vol 20 No 1 (2019)DO - 10.19087/jveteriner.2019.20.1.101, 2019)
The purpose of this study was to determine the incidence and degree of infection anisakiasis in fish catches at Fishery Seaport Muncar, Banyuwangi as an effort to prevent food borne diseases in humans. Fish samples from Muncar Beach Fishery Seaport, Banyuwangi consisted of tuna fish (Euthynnus sp.), bloated fish (Rastrelliger sp.), giant trevally fish (Caranx sp.) and snapper (Lutjanus sp.) with total amount 192 tail. Sample fish was dissected and examined the parasite by native method. Parasitic worms was fixed with 5% glycerine alcohol, stained with SemichenAcetic Carmine method, identified by key identification and calculated incidence and degree of infection. The highest incidence and degree of infection showed in Lutjanus sp. and Rastrelliger sp. 66.67% and 5.39, respectively, while the lowest showed in Caranx sp. from 6.67% and 0.09 respectively. Continue research to determine incidence and degree of infection anisakiasis in each season was required to mapping and to know the spread of worms Anisakis sp.